Oral Antidiabetic Utilization and Various Factors as an Indicator for HbA1c Control Among Patients with Type 2 Diabetes - Liberty, Iche A; Roflin, Eddy; Aziz, Muhammad; Pariyana, Pariyana; Tjekyan, Suryadi (UI Scholars Hub, 2018)
Background: Diabetes mellitus requires aggressive long-term therapy to decrease morbidity and mortality. Non-adherence to oral antidiabetic therapy represents a barrier to treatment that could lead to the deterioration of patient health. This study aimed to develop an indicator for predicting glycemic control among patients with type 2 diabetes. Methods: This unmatched case-control study recruited 110 patients from the Primary Health Care center in Palembang City. The chi-square test was used for certain variables, and multivariate analysis was performed using unconditional logistic regression to assess the effects of different variables after considering certain sociodemographic and economic characteristics as potential confounding variables. Results: The results revealed no statistically significant association of sociodemographic and economic variables (sex, age, education, and employment) with glycemic control. Family history of diabetes, duration of diabetes, body mass index, adherence, monitoring, therapy, and comorbidity were associated with glycemic control. Conclusions: Continuous education of primary care physicians is one way of improving skills for managing hyperglycemic patients. However, the challenge in treating patients with type 2 diabetes is to shift the main criterion from a disease-oriented to patient-centered approach in the context of patients' circumstances. Additionally, our developed indicator can be used as a screening test for assessing glycemic.